A logística reversa no Brasil: responsabilidade ambiental e a perspectiva econômica - Peixoto, Barthira Liandra Cordeiro (2019)
Due to the increasing severity of the environmental damages caused by irresponsible consumption and production, a need for action on global supply chains emerges in order to ensure the recycling and the extended lifespan of products. In this sense, Reverse Logistics (RL) appears as an essential tool of modern Business Logistics for changing this scenario. The present work consists of a literature review which aims to clarify the concepts of Reverse Logistics and define its limits, advantages and disadvantages, as well as the opportunities it offers for competitive advantage. The article also analyses current applications of Reverse Logistics in Brazil in order to evaluate the viability of such systems in Brazilian reality.